2010
DOI: 10.3109/03009734.2010.487164
|View full text |Cite
|
Sign up to set email alerts
|

Waterpipe (narghile) smoking among medical and non-medical university students in Turkey

Abstract: ObjectivesThis investigation was performed in order to determine the prevalence rate of waterpipe smoking in students of Erciyes University and the effects of some socio-demographic factors.MethodsA total of 645 students who study the first three grades of the medical faculty and the engineering faculty of Erciyes University were enrolled in the study. A questionnaire including 48 questions was applied. Chi-square test and logistic regression method were performed for the statistical analyses.ResultsThe total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
63
1
16

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 13 publications
13
63
1
16
Order By: Relevance
“…In the current study, 35.4% of the entire group reported waterpipe use at least once (Table 1,3). The waterpipe use among medical students was high, the risk was higher for males and last class students, and similar studies supported our results (Poyrazoglu et al, 2010, Primack BA et al, 2013, Sahin and Cinar, 2015.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, 35.4% of the entire group reported waterpipe use at least once (Table 1,3). The waterpipe use among medical students was high, the risk was higher for males and last class students, and similar studies supported our results (Poyrazoglu et al, 2010, Primack BA et al, 2013, Sahin and Cinar, 2015.…”
Section: Discussionsupporting
confidence: 89%
“…However, studies on the similar lines have already been carried out in Turkey (Poyrazoglu et al, 2010) The age of initiation of hookah smoking among the youth in Pune was found to be 17.3 years as compared to 19.2 years in Syrian students (Mazaik et al, 2004). While, a study in Pakistan (Qudsia Anjum et al, 2008) has reported that adolescents as young as 14 years old have started smoking hookah.…”
Section: Discussionmentioning
confidence: 84%
“…There are 100 million daily hookah smokers worldwide (Poyrazoglu et al, 2010). It is common in the Arabian Peninsula, China, India, Pakistan, Bangladesh, Turkey, Europe and North America.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants gave verbal consent for the use of their data for the purpose of this study. Given that the Sakarya University campus population is 14,042 and reported 32,5% (Poyrazoglu et al, 2010) prevalence of narghile smoking among university students, sample size was calculated as 887 with 5% confidence limit and 99% confidence level. Questionnaires were distributed randomly to students on Sakarya University campus .The participants completed an anonymous, voluntary, selfreport questionnaire.…”
Section: Methodsmentioning
confidence: 99%